Experimental efficiency checking of the methods aimed at forming professional lingvodidactic competence of the future masters of philology (Pedagogy of Higher and Secondary Education, 2013)
Kopus O. A. Experimental efficiency checking of the methods aimed at forming professional lingvodidactic competence of the future masters of philology.The results of the efficiency checking of the introduction of the experimental scientific-and-methodological system aimed at forming professional lingvodidactic competence of the future masters of philology are described in the article; the criteria model aimed at specifying the levels of the abovementioned competence development is proposed.
Keywords: professional lingvodidactic competence; future masters of philology; scientific-and-methodological system; criteria model